The impact of track and field training on dynapenia: gender differences in age-related decline of vertical jump performance among older adults - Fernández-Peña, Eneko; Formiglio, Eugenio; Gervasi, Marco; Benelli, Piero; Bertuccioli, Alexander; Russo, Giuseppe; Giustino, Valerio; Patti, Antonino (Frontiers in Aging, 2024)
IntroductionAlongside sarcopenia, the age-related loss of muscle strength and power, known as dynapenia, increases the risk of functional disability and mortality in older adults. However, engaging in sporting activities during old age appears to enhance functional capacity. The differences in effects between athletes and sedentary individuals, as well as between genders, have yet to be fully clarified.MethodsThe vertical jump test is recognized as a measure of lower limb performance with almost no learning effect. In the present study, we quantified age-related countermovement jump (CMJ) height loss in 120 subjects over 58 years old among both master athletes and sedentary counterparts, and analysed gender differences.ResultsBoth male and female master athletes showed significantly higher jump heights results than their sedentary counterparts (male athletes 28.5 ± 4.3 cm vs. male sedentaries 15.1 ± 5.2 cm; p < 0.01; female athletes 22.7 ± 2.5 cm vs. female sedentaries 8.2 ± 3.3 cm; p < 0.01). Female athletes were found to have higher CMJ performance than even sedentary men (p < 0.01). The rate of decline in jumping ability was the same for male athletes and non-athletes, but female athletes had the shallower rate of decline of all the groups observed (2.78 cm per decade).DiscussionSporting activity in the older age allows both men and women to perform at a higher level, with the latter also benefiting from a slower rate of decline, which can have a positive impact on functional ability and quality of life.